2017
DOI: 10.1111/joa.12761
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance thoracic ductography assessment of serial changes in the thoracic duct after the intake of a fatty meal

Abstract: The thoracic duct, a terminal lymph vessel, is thought to dilate after the intake of a fatty meal. However, this physiological change has not been well explored in vivo. Therefore, the present study aimed to assess serial changes in the thoracic duct after the intake of a fatty meal using magnetic resonance thoracic ductography (MRTD). Eight healthy volunteers were subjected to one MRTD scan before a fatty meal and eight serial MRTD scans every hour thereafter. The cross‐sectional areas of the thoracic duct we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The TD dilated significantly after a meal. This phenomenon is well known and used in the TD imaging as well as in surgery (Chen et al, 2017; Nomura et al, 2018; Robinson, 1985). It is arguable if the dilation we have seen was caused by fat absorption.…”
Section: Discussionmentioning
confidence: 93%
“…The TD dilated significantly after a meal. This phenomenon is well known and used in the TD imaging as well as in surgery (Chen et al, 2017; Nomura et al, 2018; Robinson, 1985). It is arguable if the dilation we have seen was caused by fat absorption.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are considerable individual variations making timing difficult. Although one investigation described a peak of thoracic duct enlargement approximately 3–4 hours 100 after ingestion of a high fat meal, 4–6 hours were described in a different cohort 101 . Because of the uncertainty of clinical use in a single patient and more complex logistics, the author does not routinely give high fat meals before noncontrast lymphangiography.…”
Section: Transnodal X-ray Lymphangiographymentioning
confidence: 99%
“…20 When performing noncontrast thoracic ductography, some authors have suggested improving image quality by a prior high fat meal. [100][101][102] Oral or enteral administration of, for example, cream increases flow in the thoracic duct, thereby potentially improving visibility on noncontrast MRL. However, there are considerable individual variations making timing difficult.…”
Section: Noncontrast Mrlmentioning
confidence: 99%